"My Whole Family Is Not Really My Family"—Secure Care Shadows on Family and Family Practices Among Young Adults and Their Family Members. (August 2022) - Enell, Sofia; Wilińska, Monika
This study based in Sweden explores family practices and family displays among young adults with a history of secure care, which limits and restricts contacts and therefore causes fundamental changes in relationships. Almost 10 years after institutional placement, narrations of 11 young adults and 11 nominated family members reveal ongoing struggles between imagined and lived realities of family. These struggles are revealed by memories and emotions evoked by the context of secure care and show how deeply the secure care penetrated their family lives. By using the metaphor of shadows, shadows of recalled horror of secure care (reflecting family displacement) and the pressure to make family work (reflecting restricting practices in secure care where only (birth) family were considered as family and relations of (natural) importance) are discerned. We call for more attention to the perversity of secure care arrangements, at both policy and institutional levels.